ACTIVITY OF ANTIOXIDANT ENZYMES IN SERUM OF RATS UNDER CONDITIONS OF CARRAGEENAN-INDUCED JOINT INFLAMMATION AND PROPHYLACTIC ADMINISTRATION OF CHONDROITIN SULFATE - KOT, L.; YURCHENKO, L.; SHEPELEVA, A.; DVORSHCHENKO, K. (Bulletin of Taras Shevchenko National University of Kyiv. Biology, 2025)
Among the diseases of the musculoskeletal system, the leading place is occupied by joint diseases. It is important to conduct effective prevention of these diseases in order to stop or slow down the development of pathological changes in the body. In this regard, an important issue is the search for means to restore joints. Promising in the prevention and treatment of joint diseases is the use of chondroitin sulfate, which is a natural component of the intercellular substance of cartilage. The aim of this work was to investigate the prophylactic effect of chondroitin sulfate on the activity of superoxide dismutase and catalase in rat blood serum under conditions of carrageenan-induced joint inflammation. The studies were conducted on white non-linear, sexually mature male rats weighing 180–240 g, in compliance with the general ethical principles of experiments on animals. All animals were divided into four experimental groups. The first group – control: animals sub-planar injected 0.1 ml of 0,9 % NaCl solution into the posterior right limb. The second group – animals received a therapeutic dose of 3 mg x kg-1 chondroitin sulfate daily for days daily. The third group – animals were infused intramuscularly with 0,1 ml of 0,9 % NaCl solution in the posterior right limb for 28 days and for days inflammatory edema of the limb was stimulated (animals were sub-planar injected with 0,1 ml of 1 % carrageenan solution to the posterior right limb ) The fourth group – for 28 days rats were daily intramuscularly injected with a therapeutic dose of 3 mg x kg-1 chondroitin sulfate, after which on 29th day, inflammatory edema of the limb was stimulated. The total number of animals involved in experimental studies was 40 individuals. Superoxide dismutase activity was assessed by the ability of the enzyme to compete with nitro blue tetrazolium for superoxide radicals. Catalase activity was measured by the amount of intact hydrogen peroxide in the sample. Protein content was measured by the Lowry method. It was revealed that under conditions of carrageenan-induced joint inflammation in the blood serum, the antioxidant defense system is disrupted: the activity of superoxide dismutase decreases by 1,5 times, while the catalase activity increases by 2,1 times compared to the control. Prophylactic administration of chondroitin sulfate to animals with carrageenan-induced joint inflammation contributes to the restoration of the antioxidant system.
Keywords: joint inflammation, chondroitin sulfate, superoxide dismutase, catalase, blood serum